Assessment of the economic impact of South-to-North Water Diversion Project on industrial sectors in Beijing - Yuning Gao; Miao Yu (Journal of Economic Structures, 2018)
In order to address the serious water shortage problem in northern China, China has launched the South-to-North Water Diversion Scheme, which is a large-scale inter-basin water diversion project. With Beijing as an example and using input-output analysis, this paper analyzes the macroeconomic impact of the increased water supply on the affected areas in the industrial sector. Our empirical results show that the increased water supply has brought about direct economic benefits to Beijing, which had increased from RMB 4.39 billion in 2008 to RMB 55.99 billion in 2013. The estimated full value of economic benefits had increased from RMB 14.07 billion in 2008 to RMB 231.86 billion in 2013. In addition, management of water conservancy, environment and public facilities, and public management, social security and social organization are the two main industrial sectors which drive the most direct economical benefits. This paper also forecasts the impact of the South-to-North Water Division Project on Beijing's various industrial sectors by 2020. Based on our analysis, this paper puts forward policy recommendations to further improve the efficiency of water usage in Beijing.
Keywords: 330; South-to-North Water Diversion; Input-output analysis; Water resources; Economic impact